EFEKTIVITAS IMPLEMENTASI E-BUDGETING DALAM MEWUJUDKAN GOOD GOVERNANCE DENGAN MODEL CIPP (STUDI KASUS PADA KOTA SURABAYA) - Iqbal Rafiqi; Nur Hidayah Selviyanti (Al-Amien Prenduan for Islamic Institute, 2020)
The EDGI position in Indonesia is in the range of 0.25 – 0.58 (middle-EDGI), this is certainly a demand for the government to find reliable solutions. Along with the development of the industrial era 4.0. This study aims to describe, analyze, determine the effectiveness of the implementation of e-budgeting, its operational processes and how to evaluate the fulfillment of good governance principles with the CIPP method. This study uses descriptive qualitative methods with the aim of identifying, evaluating, and interpreting previous research that is relevant to the topic. This descriptive qualitative is through the assessment of the CIPP model (Context, Input, Process and Product) in realizing good governance which is carried out by planning, conducting (conducting a review) and reporting (reporting). The literature search in this research was started by selecting articles from academic databases. The results of the study indicate that the implementation of e-budgeting in the Surabaya city government is feasible to continue because it has been proven to run effectively when viewed from the nine principles of good governance with the assessment model of four CIPP components. In the first, context, the implementation of e-Budgeting has succeeded in achieving its initial goals, namely budget transparency and accountability. Furthermore, in terms of input, the use of facilities and infrastructure as well as human resources is adequate. In terms of the process, e-Budgeting simplifies and minimizes errors in the RKA preparation process. Also, in terms of output (product), e-Budgeting improves the quality of fulfilling the nine principles of good governance.